2019
DOI: 10.3389/fnbeh.2019.00256
|View full text |Cite
|
Sign up to set email alerts
|

Functional Compartmentalization of the Contribution of Hippocampal Subfields to Context-Dependent Extinction Learning

Abstract: During extinction learning (EL), an individual learns that a previously learned behavior no longer fulfills its original purpose, or is no longer relevant. Recent studies have contradicted earlier theories that EL comprises forgetting, or the inhibition of the previously learned behavior, and indicate that EL comprises new associative learning. This suggests that the hippocampus is involved in this process. Empirical evidence is lacking however. Here, we used fluorescence in situ hybridization of somatic immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…If systems consolidation was altered during this period, extinction learning would still be retained, but the association learned during acquisition would be overwritten and hence there would be no renewal. In line with this interpretation, recent findings suggest that extinction learning and renewal engage similar hippocampal subregions and neuronal populations 13 , thus, suggesting that manipulating the hippocampus can have an impact on prior learned experience and thus, subsequent renewal.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…If systems consolidation was altered during this period, extinction learning would still be retained, but the association learned during acquisition would be overwritten and hence there would be no renewal. In line with this interpretation, recent findings suggest that extinction learning and renewal engage similar hippocampal subregions and neuronal populations 13 , thus, suggesting that manipulating the hippocampus can have an impact on prior learned experience and thus, subsequent renewal.…”
Section: Discussionmentioning
confidence: 62%
“…In particular, André and Manahan-Vaughan found that intracerebral administration of a dopamine receptor agonist, which alters synaptic plasticity in the hippocampus 12 , reduced the context-dependent expression of renewal in an appetitive ABA renewal task in a T-maze 9 . This task depends on the the specific involvement of certain subfields of the hippocampus 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Spatial appetitive EL recruits hippocampal gene encoding (Mendez-Couz et al, 2019). As yet, it is unclear to what extent this process involves hippocampal synaptic plasticity, but context-dependent forms of synaptic plasticity that are triggered by learning have been reported (Manahan-Vaughan and Braunewell, 1999;Kemp and Manahan-Vaughan, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…EL in the absence of a context change also depends on activation of the metabotropic glutamate receptor, mGlu5, whereas context-dependent EL does not (Andre et al, 2015a). Context-dependent EL recruits information processing in the hippocampus that involves gene encoding (Mendez-Couz et al, 2019), a process that has been linked to hippocampal synaptic plasticity (Kemp et al, 2013) and to context-dependent spatial learning (Hoang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…During a subsequent extinction phase, this rat can choose between at least four equally non-reinforced behaviors: turn left, turn right, return to the starting point before reaching the decision point, and refuse to leave the starting point altogether. Nevertheless, a typical analysis focuses only on the cessation of the previously conditioned response, in this case, turning right (28,29) . In this way, the effect of extinction learning on choice behavior remains undisclosed.…”
Section: Introductionmentioning
confidence: 99%